Restoration of flavonols and isoflavonoids in Ugni molinae subjected to a reciprocal transplant experiment in a domestication framework. Issue 2 (7th February 2019) - Chacón-Fuentes, Manuel; Bardehle, Leonardo; Lizama, Marcelo; Seguel, Ivette; Quiroz, Andrés
ABSTRACT: Plant domestication can modify flavonoid concentration, generating a decrease in plants subjected to cultivation, but when cultivated plants are transferred to their original wild area, flavonoids can be recovered. In this framework, a native shrub from Chile, Ugni molinae, has been domesticated due to their high phenolic composition. We hypothesised that plant domestication results in a decrease of flavonoid in cultivated plants, and that when they are exposed to a reciprocal transplant experiment, the flavonoid content can be recovered. Hence, a reciprocal transplant experiment for analysing the flavonoids of cultivated plants transferred to their original wild environments was carried out. Methanolic leaf extracts from two cultivated ecotypes and their respectively wild ancestors were collected for flavonoid analysis. Four flavonols and two isoflavonoids were identified and quantified by liquid chromatography. Results showed differences in flavonoids concentrations between wild (290 µg/g) and cultivated (160 µg/g) plants. Furthermore, when wild plants were transferred to cultivated areas, a reduction in flavonoids of 80 µg/g was observed. Moreover, rutin was the most abundant compound (36.09%) detected by chromatography in Mehuín wild plants. Our results showed that cultivated plants transferred to their respective wild environment presented a capacity of recover myricetin, daidzin and genistin content.